Effects of Revolving Doors in the Financial Sector: Evidence from Korea - Keeyoung Rhee; Sunjoo Hwang (Korea Development Institute (KDI), 2019)
The revolving door practice, i.e. the recruitment of ex-regulators by regulated firms, has long been subject to criticism in Korea. Despite its importance, however, there are few studies on the economic impact of the revolving door. By applying a unique dataset of financial firms in Korea, it was found that the practice does not improve the financial soundness of the recruiting firms. Additionally, it was observed that firms, shortly after hiring former regulators, are less likely to receive regulatory penalties. This result appears to be associated with Korea's financial supervisory system, wherein the majority of supervisory tasks are concentrated within a single agency. - Despite the public's criticism, there have been few empirical studies on the effects of the 'revolving door' practice. - This study provides analysis of the economic impact of the revolving door for financial regulators in Korea. - The 'expertise hypothesis' argues that former financial officials can contribute to improving the risk management of recruiterfirms due to the officials'expertise. - The 'collusion hypothesis' claims that financial firms recruit former officials to seek unduly gains, such as evading regulatory enforcement. - The empirical analysis found no indications of improvement in financial risk management performance after the appointment of former financial officials. - The probability of receiving regulatory action after hiring ex-FSS regulators as executives decreases 16.4% and it is statistically significant, while the probability does not change significantly after hiring ex-regulators from other institutions. - It is possible that executives who were formly in the FSS can help manage the nonfinancial risks. But, the empirical analysis found no indications of such a contribution when the probability of regulatory action decreased. - In the US, financial companies with former financial officials as executives exhibited noticeable improvements in their financial soundness while no meaningful changes were found in the probability of regulatory action. - Unlike the US' decentralized task structure run by multiple authorities, Korea's financial supervisory tasks are concentrated in a single institution. - According to relevant studies, such a centralized structure could incur more incentives for collusive ties between the pertinent government authority and financial firms.
Keywords: 330